Detecting the Effect of Umckaloabo/EPs®7630 Liquid Extract after its Therapeutic Purposed Usage in Calves Showing Symptoms of Respiratory Tract Infection - Ak, Ahmet; Kale, Mehmet (Acta Scientiae Veterinariae, 2017)
Background: Respiratory tract diseases are commonly seen in beef cattle. Young calves are affected with many respiratory pathogens. Viral pathogens are particularly seen. There are many causative factors, e.g. environmental conditions, immune system of calves. Therefore, alternative treatments are needed for viral respiratory infections. The purpose of the current study was to investigate effectiveness of Umckaloabo/EPs®7630 liquid extract in some bovine viral pathogens of young beef calves. Materials, Methods & Results: Antibody presence in terms of bovine herpesvirus type 1 (BHV-1), bovine viral diarrhea virus (BVDV), bovine parainfluenza virus type 3 (BPIV-3), bovine respiratory syncytial virus (BRSV) and bovine adenovirus type 3 (BAV-3) was searched in blood serum samples of 40 Holstein calves aged 6 months and over showing respiratory tract infection symptoms. All animals were found seronegative in terms of other factors except BRSV. Out of 20 BRSV seropositive calves, 10 of them were classified as control group and the other ten as testing group. BRSV antibody titers were also detected in blood samples of both groups on day 0. Umckaloabo/EPs®7630 liquid extract was given through oral route to animals in testing group according to their weights for 14 days morning, noon and night. No application was performed on animals in control group. BRSV antibody titers were detected in blood samples of animals in both groups taken on days 1st, 3rd, 5th, 7th, 10th and 14th. At the end of day 14th, BRSV antibody titer increased in 9 out of 10 animals (90%) in testing group that were given Umckaloabo/EPs® 7630 liquid extract while one of them (10%) showed no variability. BRSV antibody titer increased in 6 out of 10 animals (60%) in control group while it decreased in one of them (10%) and 3 of them (30%) showed no variability. In testing group, BRSV antibody titer started to increase on day 3rd in 6 out of 10 animals (60%), on day 5th in one (10%), on day 10th in one (10%) and on day 14th in another (10%). In control group, BRSV antibody titer started to increase on day 3rd in 3 out of 10 animals (30%) and on day 5th in 3 of them (30%). When haematologic values of blood samples taken from animals in testing and control groups on day 14th were studied comparatively, no statistical importance (P < 0.01 or P < 0.05) and difference was detected. As a result, in stock calves showing respiratory tract infection symptoms, applying Umckaloabo/EPs® 7630 liquid extract helped BRSV antibody titer to increase and symptoms decreased. The increase in antibody titers started from day 3rd especially after applying Umckaloabo/EPs® 7630 liquid extract. Discussion: Respiratory system infections are contagious and fatal in calves. Respiratory tract bacterial and viral vaccinations are applied in order to prevent losses of calves due to these problems. However, these vaccinations are not sufficient most of the time and antibiotics+supportive treatment applications follow afterwards. Therefore, we advise to use a herbal product, Umckaloabo/ EPs®7630 liquid extract, that has both an antiviral efficiency and a feature of supporting immune system in order to prevent mortalities in stock calves, to stop the infection from spreading on all the herd and to decrease the symptoms of respiratory system. We believe that the obtained data should be supported with more examples and more wide-ranging studies.